Assessment of anxiety, sleep quality, and cognitive functions in underweight young adults: A pilot study - Saieesha Chowdary Kolla; Aalasyam Naveen; Prakhya Chowdary Koya; Vikash Sharma; Sravani MR; Shyma Parapurath (Asian Journal of Medical Sciences, 2025)
Background: It was documented that increased body mass index is associated with cognitive function deficits, in addition to cardiovascular diseases, diabetes mellitus, and insulin resistance. Weight was reported to improve physical activity and, thereby, improve cognitive functions. Weight reduction in patients with cognitive disorders helped to improve the same.